Impact of high-speed rail on intercity travel behavior change: The evidence from the Chengdu-Chongqing Passenger Dedicated Line - Ren, Xiaohong; Chen, Zhenhua; Wang, Fang; Wang, Jiamei; Wang, Chunyang; Dan, Ting; Du, Zongyang (Journal of Transport and Land Use, 2019)
This paper investigates the impact of high-speed rail (HSR) on intercity travel behavior changes using the Chengdu-Chongqing (Chengyu) Passenger Dedicated Line (PDL) as an example. Based on the statistical analysis of survey data that consists of 1384 samples, the result shows that HSR has become the primary mode of intercity travel between Chengdu and Chongqing. Specifically, travel demand has increased by 60% after the operation of the HSR system and the demand change is affected by several factors, such as trip purpose, gender, and travel time savings. The result also shows that the variation of travel demand in both directions declined after the opening of HSR, which suggests that HSR tends to promote a convergent growth of intercity travel demand. Although most passengers ride the Chengyu HSR for a personal reason, the number of riders using it for commuting and business purposes has also increased substantially. Overall, the study confirms that the economic link between Chengdu and Chongqing has been enhanced by the operation of HSR.